Analysis of Training Methods for Passing Accuracy in Futsal Sports: Systematic Literature Review - Kuroma, Rafsan Zidan; S, Adi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The objective of this study was to analyze training methods that can improve passing accuracy in futsal. Materials and methods: The PRISMA table will be used for systematization and meta-analysis in this observational investigation. Various studies were published from January 2020 to December 2024. In the search procedure, the following keywords were used: (1) Futsal and (2) Training. The search in this study used the Scopus research journal database. The overall theme of this study was obtained 42. Contains 19 articles, and then 10 relevant articles were taken. Based on the research that has been done, the researcher found that the Small-sided Games (SSG) training method is a valid and reliable training method and has been proven to improve the quality of passing in futsal. The SSG training method can also increase VO2 Max which will also affect the quality of players in futsal games. This study also found a valid and reliable instrument or test tool in the form of change of direction speed (CODS) and reactive agility (RAG) to measure the quality of basic passing techniques in futsal.